Design of an Arduino-Based Boat Roll Stabilizer System Prototype Using MPU6050 Sensor - Sitompul, Erwin; Prabowo, Andri Setia; Tarigan, Hendra; Suhartomo, Antonius (PTE FTK UIN Ar-Raniry, 2024)
In the midst of lakes or oceans, boats used for recreational fishing that are left immobile are more vulnerable to rolling waves or wind. This study was conducted to develop a prototype of the boat's stabilization system and control scheme in order to address the stability issue with the craft. Based on the prototype concept, a small boat was constructed with a control loop that included two DC motors, a motor driver, a gyroscope MPU6050, and an Arduino Uno microcontroller. A prototype stabilizer was used to evaluate two different sets of control parameters, and in both situations the stabilizer was able to provide the boat with critical interference before bringing it back to a vertical position. PWM 1 level change rate (Pulse-Width-Modulation) yields better results than 4 level change rates (PWM), with faster stabilization achievement. (1,12 seconds versus 2,46 second). In the development of the prototype, it is necessary to test the implementation of the system on the boat to the actual size.